(untitled) (Fiep Bulletin - online, 2015)
The purpose of this study was to discuss the impact of a continuing education program on the expressions manifested by Physical Education teachers on the inclusion theme. Ten Physical Education teachers who belonged to the municipal public schools in Londrina, State of Paraná, participated in this study. Among them there were two teachers who did not deal with students with any kind of deficiency and the others dealt with students in inclusion situation or in special classes. The focus group was adopted as the procedure for the data gathering. The data were gathered from 16 fortnight meetings that occurred during 2003 on Fridays with a four-hour duration. By means of collective interviews, recorded on tape and afterwards transcribed, the participants’ expressions concerning the inclusion theme, were obtained. The results obtained on the occasion of the focus group enabled us to notice the shifting of the teachers’ expressions from more external aspects to those that are closer to the school daily routine specially to what the school’s responsibility is concerned. The interactions resulting from the dynamics proposed for the direction of the group suggest that, besides enriching the understanding of the continuing education, special attention must be given to the research method to be adopted. It is essential not to lose sight of the effective participation of the basic education teachers in the overcoming of conflicts triggered in the school routine.